HSC Honest Broker Service, Applying the Health Data Research UK Transparency Guidelines in Northern Ireland - Harbinson, Alan; Coey, Rachel (International Journal of Population Data Science, 2024)
Background The HSC Honest Broker Service is the Secure Data Environment for Northern Ireland. As processors of citizens data we are committed to openness and transparency and have worked with Health Data Research UK on new initiatives like the Health Data Research Innovation Gateway and the development and publication of Data Use Registers. Receiving funding through the Transparency Award has allowed us to make further improvements to our online content, to help align with the Transparency Standards. We aim to make our service easily understandable for the general public as well as providing as much information as possible to researchers so that they know what to expect when making an application to access Health and Social Care Northern Ireland data. Aim We provide access to de-personalised Health and Social Care records for approved researchers, within a Secure Data Environment. As an established service we had a lot of online content in place which met the Transparency Standards however areas we felt we could improve on were: Standard 2 Transparent application process and criteria Standard 3 Clear website navigation Standard 4 Consider Target Audience Standard 5 Regular review of website content Methods Under the project we carried out the following activities: Internal review of website, application materials and guidance, other public facing documents in line with the Transparency Standards Review of best practice, looking at content from other equivalent services across the UK as well as key resources such as the understanding patient data website Engagement with internal Comms Team around improvements to website layout and functionality Commissioning of explainer videos with the internal Comms Team Working with Comms Team on a glossy promotional document which will be used for multiple purposes over time, including sending to Universities across UK. Results Updated Website Better Structure Tailored Content for Public and Researchers Explainer videos Promotional 12 page document explaining the service and how to apply Review of guidance documents on application and approval process Engagement with local patient representative group to commission lay review of public facing materials (upcoming) Conclusion We feel that our new web content is significantly improved as a result of this exercise. Short focused investment to help improve on a specific subject area like transparency was welcome and a very useful motivator, more work will be needed to continue to improve and act on feedback we will receive on the new materials. We have established a better relationship developed with communications lead within organisation by working with them on this project. This project has also helped that team grow their capacity and show case what they can do for the wider organisation. Lots of good practice out there across various equivalent services. Additional Web Analytics purchased will be very useful to provide feedback on how users are navigating the site and where they are coming from. Around 40% of users on the main website are accessing through mobile devices so it is important to take this into consideration when designing content.